(3cTa GdCSQGQ h gJc GdCSJGQs - (3LeGd GdOjf Hf gdGd GdUaOj,J (B696 (3g` s
(3ChdgG (B:s
(3Chd GdbQBf s
(3BNQgG (B:s
(3BNQ ShQI GdfSGA s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B256s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B37 s
Keywords: (3GdJaSjQ hYdhe GdbQBfs